Teacher voices matter: The role of teacher autonomy in enhancing job satisfaction and mitigating burnout. - Cheyeon Ha; Tim Pressley; David T Marshall (PLoS ONE)
This study aims to explore variables associated with teacher burnout at the end of the 2021-2022 school year and shed light on teachers' mental health issues related to psychological factors. We collected survey data from 824 United States teachers. Using a moderated mediation analytic model, the results of this study showed that teachers' autonomy had considerable interaction effects on job satisfaction and burnout with other variables in this study (i.e., administrative support on job satisfaction and job satisfaction on burnout). Teachers with more experience and higher job satisfaction showed lower burnout scores. Furthermore, results showed significant relationships between key variables influencing burnout. These findings are key as teacher attrition grows across the United States, and school leaders should look to support teachers' well-being.